2012
DOI: 10.1097/fbp.0b013e32834eafe6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sigma-1 receptor modulators on ethanol-induced conditioned place preference in the extinction–reinstatement model

Abstract: Sigma-1 receptor agonists are reported to augment and antagonists block the rewarding effects of drugs of abuse. However, their effect on reinstatement of ethanol-induced conditioned place preference (CPP) has not yet been explored. Therefore, we investigated the ability of 2-(4-morpholino)ethyl-1-phenylcyclohexane-1-carboxylate (PRE-084), a sigma-1 receptor agonist, and N-[2-(3,4-dichlorophenyl)ethyl]-N-methyl-2-(dimethylamino) ethylamine dihydrobromide (BD-1047), a sigma-1 receptor antagonist, on the acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…σR antagonists and antisense oligonucleotides ameliorate cocaine-induced convulsions, lethality and locomotor activity ( 49 , 50 ), as well as sensitization, and conditioned place-preference in rodents ( 51 ). They also reduce alcohol consumption in alcohol-drinking rats ( 52 , 53 ) and Swiss mice ( 54 ). Interestingly, the interaction of fluvoxamine [Luvox], a selective serotonin reuptake inhibitor [SSRI], and the σRs may account for its potential amelioration of psychotic depression ( 55 , 40 ), where increased glutamate [Glu] release occurs through activation of serotonin [5-HT 3 ] mediated by σ 1 Rs ( 56 ), and in patients with schizophrenia ( 57 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…σR antagonists and antisense oligonucleotides ameliorate cocaine-induced convulsions, lethality and locomotor activity ( 49 , 50 ), as well as sensitization, and conditioned place-preference in rodents ( 51 ). They also reduce alcohol consumption in alcohol-drinking rats ( 52 , 53 ) and Swiss mice ( 54 ). Interestingly, the interaction of fluvoxamine [Luvox], a selective serotonin reuptake inhibitor [SSRI], and the σRs may account for its potential amelioration of psychotic depression ( 55 , 40 ), where increased glutamate [Glu] release occurs through activation of serotonin [5-HT 3 ] mediated by σ 1 Rs ( 56 ), and in patients with schizophrenia ( 57 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…CPP reactivation procedures have been successfully applied in conjunction with abstinence manipulations following which drug injections or stress reactivate CPP. (e.g., Buthada et al 2011a,b; Itzhak and Martin 2002; Kuzmin et al 2003; Mueller and Stewart 2000; Romieu et al 2004; Szumlinski et al 2002; Thanos et al 2009; for review see Aguilar et al 2009; Tzschentke 2007) .…”
Section: 0 Models Of Craving and Relapse Associated With Conditionmentioning
confidence: 99%
“…The systemic administration of the selective Sig-1R agonist PRE-084 prior to ethanol enhances ethanol-induced CPP (Maurice et al, 2003). Studies using intracerebroventricular administration of the same agonist also showed a facilitation of the acquisition of ethanol-induced CPP (Bhutada et al, 2012). Moreover, pretreatment with the Sig-1R antagonist BD-1047, administered during conditioning, blocks the acquisition of ethanol-induced CPP (Maurice et al, 2003), while its intracerebroventricular administration has been shown to reduce both acquisition and expression (Bhutada et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Studies using intracerebroventricular administration of the same agonist also showed a facilitation of the acquisition of ethanol-induced CPP (Bhutada et al, 2012). Moreover, pretreatment with the Sig-1R antagonist BD-1047, administered during conditioning, blocks the acquisition of ethanol-induced CPP (Maurice et al, 2003), while its intracerebroventricular administration has been shown to reduce both acquisition and expression (Bhutada et al, 2012). Lastly, neither Sig-1R agonists nor antagonists affect place preference when administered alone (Romieu et al, 2000; Maurice et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation